Convenient synthesis of benzo[4, 5]thiazolo[2, 3-c][1, 2, 4]triazoles with 1 mol% CuCl2·2H2O as catalyst in water. Issue 3 (18th December 2014) - Wen, Li-Rong; Li, Shou-Lei; Zhang, Jian; Li, Ming
Abstract : A synthesis of benzo[4, 5]thiazolo[2, 3- c ][1, 2, 4]triazoles has been developed from hydrazides and o -bromo-arylisothiocyanates with 1 mol% CuCl2 ·2H2 O as catalyst in water. Abstract : A convenient and efficient procedure for the synthesis of benzo[4, 5]thiazolo [2, 3- c ][1, 2, 4]triazoles has been developed via a tandem intermolecular C–N bond and intramolecular C–S bond formation sequence from o -bromo-arylisothiocyanates and aroylhydrazides. A series of benzo[4, 5]thiazolo[2, 3- c ][1, 2, 4]triazoles were provided in excellent overall yields with 1 mol% CuCl2 ·2H2 O/1 mol% 1, 10-phenanthroline as the catalyst and water as the solvent.